PROSES KREATIF PENGARANG CHICKLIT DAN TEENLIT INDONESIA - Noor, Redyanto (HUMANIKA, 2015)
An author creative processÂ  includes the issue of why and how the author wrote the novel. Among the chicklit and Teenlit novelists there are similar supporting factors, namely talent, hobby, intelligence, and daily life experience around them. The Supporting factors are then combined with skills, methods and storytelling which spontaneous and honest.They never thought about storytelling techniques when writing a novel. They do not think about the structure of fiction such as the grooves, figure-characterizations, backgrounds, storytelling, and so on.The creative process of the authors can not be separated from the influence of life in their surrounding environment that provides reality as a source of inspiration to write the story. The reality is in the form of social problems, personal problems, society, humanity, divinity, and so on. All sorts of information and experience are gained through association and access to information technology. All are quickly and simultaneously enrich the treasury of their knowledge so that they can talk anywhere, anytime, and about anything. Thus, the young chicklit and Teenlit novelists become successful and famous is not in a sudden and without a process. Nor because special facilities given by publisher or certain parties, but through hard work. Lot of terms and conditions that they can meet through their struggle.Thus, it can be concluded that the creative process of chicklit and Teenlit novelist is a blend of natural talent, hobby, intelligence, and life experience, supporting by intelligence, hard work, a wealth of experience, breadth of relationships, social sensitivity, the ability of storytelling and writing skills.